Ovulation Induction, Pregnancy and Delivery in a Patient with Partial Hypopituitarism due to Lymphocystic Hypophysitis: A Case Report - Ezechi, OC; Ezeobi, PM; Nwokoro, CA (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Lymphocystic hypophysitis is an unusual autoimmune disease that causes partial or total hypopituitarism and often associated with chronic anovulation. We report a case of ovulation induction, uneventful pregnancy and vaginal delivery in one of our patient with lymphocystic hypophysitis. Key words: Lymphocystic hypophysitis, chronic anovulation and ovulation induction. doi:10.3126/njog.v3i1.1440 NJOG 2008 May-June; 3(1): 46 - 48